LEBESGUE’S CRITERION FOR INTEGRABILITY - Bayu Riyadhus Saputro; Sumaji . (Universitas Muhammadiyah Ponorogo, 2018)
Lebesgue integral was defined constructively by using outer measure, measurable set, measurable function and Lebesgue measure concept. Then it was constructed by using simple function. The requirement of a Lebesgue integrable function to be Riemann integrable is bounded function and the set of discontinuities of that function has measure zero.